2017
DOI: 10.1126/scisignal.aaf8223
|View full text |Cite
|
Sign up to set email alerts
|

Reduced abundance of the E3 ubiquitin ligase E6AP contributes to decreased expression of the INK4/ARF locus in non–small cell lung cancer

Abstract: The tumor suppressor p16, one protein encoded by the INK4/ARF locus, is frequently absent in multiple cancers, including non-small cell lung cancer (NSCLC). Whereas increased methylation of the encoding gene (CDKN2A) accounts for its loss in a third of patients, no molecular explanation exists for the remainder. We unraveled an alternative mechanism for the silencing of the INK4/ARF locus involving the E3 ubiquitin ligase and transcriptional cofactor E6AP (also known as UBE3A). We found that the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 45 publications
3
34
0
Order By: Relevance
“…In our recent study published in Science Signaling we addressed, at least in part, this gap in knowledge. 1 We unraveled a novel mechanism for the reduction of p16, involving the E3 ubiquitin ligase and transcriptional cofactor, E6-associated protein (E6AP), which we found to be lowly expressed in certain NSCLCs.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent study published in Science Signaling we addressed, at least in part, this gap in knowledge. 1 We unraveled a novel mechanism for the reduction of p16, involving the E3 ubiquitin ligase and transcriptional cofactor, E6-associated protein (E6AP), which we found to be lowly expressed in certain NSCLCs.…”
Section: Commentarymentioning
confidence: 99%
“…In our recent study published in Science Signaling we addressed, at least in part, this gap in knowledge. 1 We unraveled a novel mechanism for the reduction of p16, involving the E3 ubiquitin ligase and transcriptional cofactor, E6-associated protein (E6AP), which we found to be lowly expressed in certain NSCLCs.Our analysis identified E6AP as a positive regulator of the INK4/ARF locus. Mechanistically, we showed that E6AP controls this locus by reducing the ability of E2F transcription factor 1 (E2F1) to bind to the cell division control protein 6 (CDC6) promoter.…”
mentioning
confidence: 99%
“…Dysregulation of E6AP expression and function has been associated with numerous diseases such as cervical carcinogenesis, Angelman syndrome and others . In a recent study E6AP was shown to act as a tumor suppressor in non‐small cell lung cancer by maintaining INK4/ARF expression levels . Mansour et al showed that E6AP suppressed breast cancer invasiveness, colonization, and metastasis in mice as well as in breast cancer patients while E6AP loss was associated with poor prognosis, particularly for basal breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…E6AP was initially identified in the context of high risk human papillomavirus (HPV)-related cancers, where E6AP in association with viral oncoprotein E6 ubiquitinates and degrades the tumor suppressor p53 (6). Recent work from our group and others reveal roles of E6AP in HPV-independent cancers, including lung and blood cancer (7,8). E6AP functions as an E3 ligase and as a transcriptional cofactor (9).…”
mentioning
confidence: 99%
“…The functions of E6AP, mostly attributed to its ligase activity include cellular growth, cell cycle, apoptosis, cellular senescence, cellular stress response and proteasomal regulation (10 -16). Independent of its E3 ligase activity, E6AP also coactivates transcription by the steroid hormone receptors and by E2F1 (7,9,17).…”
mentioning
confidence: 99%